DO NOT LOSE SIGHT OF SYPHILIS. (February 2015) - Nejat, Maryam; Murdoch, David
Abstract : Ocular manifestations of syphilis are uncommon and typically occur during the secondary stage of the disease, causing significant sequelae if left untreated. This is an unusual presentation of syphilis in a 36-year-old man. He was referred by his optometrist to an ophthalmologist with a five day history of central and para-central bilateral visual field loss preceded by two days of photopsia. There were no other accompanying symptoms, including headache, nausea, ocular pain, nor other focal neurological deficits. However, he had experienced a Jarisch-Herxheimer reaction after receiving cefazolin prophylaxis prior. On examination, he had greatly reduced vision in both eyes, markedly on the left eye with acuity of 6/60 and bilateral optic discs swelling. He had negative HIV, hepatitis B and C serology, but syphilis serology had positive RPR, EIA and TPHA. MRI examination of the brain and orbits was unremarkable except for inflammatory changes in the mastoids. A diagnosis of bilateral treponemal optic neuritis was made, and he was commenced on oral prednisone for 3 days and intravenous penicillin G for 2 weeks and his visual acuity improved markedly.